Influência de semioquímicos emitidos por plantas de arroz no comportamento de Tibraca limbativentris, Glyphepomis spinosa (Heteroptera: Pentatomidae) e Telenomus podisi (Hymenoptera: platygastridae) - Ulhoa, Lucas Adjuto (2018)
Tibraca limbativentris Stål is one of the stink bugs most harmful to rice cultivation in Brazil, mainly in irrigated environment. Glyphepomis spinosa Campos & Grazia is a stink bug of secondary economic importance, but often occurs in rice fields in the Midwestern and Northern regions of Brazil. To defend against these stink bugs, plants can emit volatile organic compounds that act directly as repellent or as toxic substances, or indirectly, by attracting natural enemies. Studies on chemical communication between insects and plants are fundamental to understand the host searching process, and can be used to manage insect pests and natural enemies in the field. The objectives of this work were to identify the constitutive and herbivore - induced volatile organic compounds emitted by rice and to evaluate the influence of these volatiles on the searching behavior of the stink bugs T. limbativentris and G. spinosa and their natural enemy, the egg parasitoid Telenomus podisi Ashmead. The volatiles were collected from rice (BRS Pampa) without injury and with injury imposed by two virgin females (adults) of T. limbativentris and G. spinosa, for up to 144 hours. The samples were analyzed by gas chromatography coupled to a flame ionization detector (CG-FID) and gas chromatography coupled to mass spectrometry (GC-MS). The responses of virgin and mated females of T. limbativentris and G. spinosa and virgin females of T. podisi were evaluated in a "Y-tube" olfactometer. The rice plants responded to injury producing volatiles, especially the sesquiterpenoids. Virgin females of T. limbativentris preferred heathy plants and air (control without plants) than by injured plants. Virgin females of G. spinosa females preferred air than by injured plants. The egg parasitoids T. podisi preferred injured plants by T. limbativentris than by healthy plants. T. podisi also preferred injured plants by G. spinosa than by air. The results show that rice plants release defense compounds that act directly repelling the stink bugs T. limbativentris and G. spinosa and indirectly attracting the natural enemy T. podisi.